A novel route discovery procedure for congestion avoidance in multi-hop WSNs. (2017) - Chughtai, Omer; Badruddin, Nasreen; Awang, Azlan; Rehan, Maaz
Due to high data traffic and resource-constrained nature of the wireless sensor network (WSN), congestion occurs which leads to severe packet loss and high energy consumption. Since an efficient route discovery procedure can avoid congestion and balance the traffic load, a reliable congestion-aware routing is important and requires careful design consideration. In this paper, a novel route discovery procedure for congestion avoidance (RDCA) in multi-hop WSNs has been proposed. RDCA is based on an objective function that incorporates the implicit behaviour of traffic load and consumed energy of the sensor nodes and signal strength between them along with the hop count. The results show that RDCA has a significant impact over energy, traffic load, and link quality aware ad hoc routing (ETLAODV) and energy efficient and QoS based routing (EQSR) in terms of packet delivery ratio (PDR), end-to-end (ETE) delay, energy consumption, and throughput.